2020
DOI: 10.1016/j.electacta.2020.135997
|View full text |Cite
|
Sign up to set email alerts
|

Flower-like NiCo2O4–CN as efficient bifunctional electrocatalyst for Zn-Air battery

Abstract: Bifunctional transition metal oxide based electrocatalysts play an important role in oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) for rechargeable metal-air batteries. Herein, we synthesize a kind of three-dimensional (3D) flower-like composite catalyst with NiCo 2 O 4 and N doped carbon (NC) derived from g-C 3 N 4 , under hydrothermal conditions. The best NiCo 2 O 4-CN catalyst shows a hierarchical structure composed of interconnected nanosheets, and exhibits versatile bifunctional ORR/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 57 publications
1
36
0
Order By: Relevance
“…In addition, recent studies have shown that bimetallic oxide catalysts exhibit higher activity than single metals. Yu and co-workers [106] developed nitrogen doped carbon incorporated 3D flower-like NiCo 2 O 4 composites by hydrothermal method, whereas the N-doped carbon was obtained by using g-C 3 N 4 as raw materials. Results demonstrate that the 3D electrode exhibited good ORR/OER bi-functional activity with an E 1/2 value of 0.81 V and overpotential of 383 mV to deliver 10 mA cm À 2 .…”
Section: D Electrodes For the Bi-functional Oxygen Electrocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent studies have shown that bimetallic oxide catalysts exhibit higher activity than single metals. Yu and co-workers [106] developed nitrogen doped carbon incorporated 3D flower-like NiCo 2 O 4 composites by hydrothermal method, whereas the N-doped carbon was obtained by using g-C 3 N 4 as raw materials. Results demonstrate that the 3D electrode exhibited good ORR/OER bi-functional activity with an E 1/2 value of 0.81 V and overpotential of 383 mV to deliver 10 mA cm À 2 .…”
Section: D Electrodes For the Bi-functional Oxygen Electrocatalysismentioning
confidence: 99%
“…One of the key targets for the noble metal-based catalysts is to reduce their loading, and meanwhile, maintain or even increase the overall activities relative to ORR and OER by incorporation of non-precious metal or metal-free composition. Most of the transition metal-based materials (e. g., oxides, [9][10][11] sulfides, [12][13][14][15] spinels, [16][17][18][19] macrocyclic compounds, [20][21][22] perovskites, [23][24][25] metal-NC catalysts, [26][27][28] ) and metal-free materials feature are earth abundant and cheap in price, which can be easily scalable. However, the relatively inferior catalytic activity severely hindered their practical application in energy related devices.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, spinel oxides (AB 2 O 4, where A and B are transition metal ions) are explored as electrocatalyst for the ORR/OER to use in metal‐air battery. In the spinel structure of AB 2 O 4 formula, the B 3+ and A 2+ metal ions which occupy in the octahedral and tetrahedral sites, respectively, act as reaction centers to promote the ORR/OER rates . However, the spinel‐oxide catalysts are associated with poor cyclability and still limited electrocatalytic activities.…”
Section: Introductionmentioning
confidence: 99%
“…[1,[7][8][9][10][11][12][13][14][15][16][17][18] Heteroatom doped carbon nanostructures are well known for ORR. [2,[19][20][21][22][23][24][25][26][27][28][29] Further, incorporating metal/ alloy improves the ORR activity. [29][30][31] Reports suggest that metal-nitrogen coordination (M-N x ) centers are highly beneficial for ORR and HER.…”
mentioning
confidence: 99%
“…[2,[19][20][21][22][23][24][25][26][27][28][29] Further, incorporating metal/ alloy improves the ORR activity. [29][30][31] Reports suggest that metal-nitrogen coordination (M-N x ) centers are highly beneficial for ORR and HER. [32][33][34][35][36][37] Transition metal nanoparticles supported on N-doped carbon have been extensively studied for HER.…”
mentioning
confidence: 99%